Cultivating Competence: Bridging Professional Gaps in Bandung’s Buruan SAE Urban Farming Program: Membangun Kompetensi: Menjembatani Kesenjangan Profesional dalam Program Pertanian Perkotaan SAE Buruan, Bandung - Fajaryah, Mellania Rima; Pradesa, Hafid Aditya; Listiani, Teni; Jubaedah, Edah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Urban farming programs require adaptive human resource competencies to support food security and community empowerment in complex environments. Specific Background This study examines agricultural extension workers within an urban farming program, focusing on competency alignment with role demands across different job levels. Knowledge Gap Limited evidence exists on how competency gaps are systematically mapped and translated into operational development strategies in urban agriculture contexts. Aims The study aims to identify competency gaps and formulate a structured competency development framework based on empirical findings. Results Findings reveal consistent gaps where competency achievement falls below importance levels, particularly in agribusiness management, agroprocessing, commercialization, institutional development, and technology facilitation, while communication and leadership competencies remain relatively strong. These gaps vary by job level, with higher-level roles demonstrating more complex deficiencies. Importance–Performance Analysis highlights priority competencies requiring immediate attention. Novelty The study integrates job-level competency gap mapping with Importance–Performance Analysis and operationalizes the results into a 70:20:10 learning framework for targeted capacity development. Implications The findings suggest that competency development must be differentiated by role complexity and prioritize strategic technical skills through experiential, social, and formal learning to support sustainable urban farming programs. Highlights• Strategic technical competencies show the largest performance gaps• Priority skills cluster in agribusiness, processing, and technology facilitation• Development strategy aligns learning modes with competency gap structure KeywordsAgricultural Extension; Competency Gap; Urban Farming; IPA Analysis; Learning Model